2010
DOI: 10.1007/s10548-010-0157-7
|View full text |Cite
|
Sign up to set email alerts
|

Scalp-Recorded Induced Gamma-Band Responses to Auditory Stimulation and Its Correlations with Saccadic Muscle-Activity

Abstract: We previously showed that the transient broadband induced gamma-band response in EEG (iGBRtb) appearing around 200-300 ms following a visual stimulus reflects the contraction of extra-ocular muscles involved in the execution of saccades, rather than neural oscillations. Several previous studies reported induced gamma-band responses also following auditory stimulation. It is still an open question whether, similarly to visual paradigms, such auditory paradigms are also sensitive to the saccadic confound. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
7
28
0
Order By: Relevance
“…For example, they analyzed their data on a trial-by-trial basis, and found that microsaccades nearly always produced a transient burst of gamma band activity ~4 ms later. It was also found that the iGBR all but disappeared on trials where microsaccades were absent (see Yuval-Greenberg & Deouell, 2011 for comparable results with auditory stimuli).…”
Section: Introductionmentioning
confidence: 65%
“…For example, they analyzed their data on a trial-by-trial basis, and found that microsaccades nearly always produced a transient burst of gamma band activity ~4 ms later. It was also found that the iGBR all but disappeared on trials where microsaccades were absent (see Yuval-Greenberg & Deouell, 2011 for comparable results with auditory stimuli).…”
Section: Introductionmentioning
confidence: 65%
“…This artifact has previously been acknowledged as a transient problem in response to stimulus onset (Yuval-Greenberg et al, 2008; Keren et al, 2010; Hassler et al, 2011; Schwartzman and Kranczioch, 2011; Yuval-Greenberg and Deouell, 2011). Our results show that, for non-stationary stimulation and cognitive demands, the saccadic spike artifact is not limited to a transient signal distortion, but can induce a persistent modulation of gamma-band activity.…”
Section: Discussionmentioning
confidence: 96%
“…Ocular muscle contractions at microsaccade onset induce “spike potentials” in the EEG with maximum power in the gamma band at parietal electrodes (Thickbroom and Mastaglia, 1985; Riemslag et al, 1988; Yuval-Greenberg et al, 2008; Keren et al, 2010; Carl et al, 2012). Furthermore, microsaccade rate shows a characteristic suppression-enhancement sequence following visual stimulus transients and is also modulated by cognitive factors (Engbert and Kliegl, 2003; Rolfs et al, 2008; Yuval-Greenberg and Deouell, 2011). Together, spike potentials mimic transient gamma-band activity of neuronal origin, and are thus highly problematic for studying visually gamma-band activity with EEG.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that both in the visual (Yuval-Greenberg et al, 2008) and auditory domains the induced GBR is susceptible to contamination by spike potentials generated by micro-saccadic eye movements (Yuval-Greenberg and Deouell, 2011). A correlation between gamma band activity and saccadic rate was observed, both showing a stereotypical decrease of activity after sound onset followed by a sustained increase 200–300 ms after sound onset.…”
Section: Discussionmentioning
confidence: 99%